The kitchen fire prevention system using a global system for mobile - Rosnee Ahad; Nur Amani Lowe Mohd Shafiq Lowe; Mohamad Zaid Mustafa; Sri Sumarwati (Faculty of Engineering, Universitas Negeri Yogyakarta, 2021)
Fire is one of the disasters that cause property loss and casualties. Based on statistical analysis, the cases related to Liquefied Petroleum Gas (LPG) fires caused by the stove, are repeated every year. There is no fire prevention system in the house, usually in the kitchen, applied as a safety and prevention measure to prevent fire. Therefore, this quantitative study aims to develop a prototype of the kitchen fire prevention system using the Global System for Mobile (GSM) modem to reduce the risk of fire in the living room caused by the kitchen appliances. The development of this project refers to the five steps in the Software Development Life Cycle (SDLC) method which is needs analysis, design, implementation, testing, and evaluation. The results show that the prototype combines two types of sensors namely MQ135, and LM35, where it works simultaneously in two conditions. Under